Diversity and evolution of sexually dimorphic mental and lateral glands in Cophomantini treefrogs (Anura: Hylidae: Hylinae). (14th November 2014) - Brunetti, Andrés E.; Hermida, Gladys N.; Luna, María Celeste; Barsotti, Adriana M. G.; Jared, Carlos; Antoniazzi, Marta Maria; Rivera‐Correa, Mauricio; Berneck, Bianca V. M.; Faivovich, Julián
<x xml:space="preserve">Abstract</x> We describe the structure and histochemistry of mental and lateral glands in a representative array of 28 species of five genera of the Neotropical hylid frog tribe Cophomantini. Structural diversity was coded in 15 characters that were optimized on the most recent phylogenetic hypothesis. Mental and lateral glands occur in 17 species and 10 species, respectively, whereas nine species have both. Each glandular concentration may have two types of sexually dimorphic skin glands (SDSGs), specialized mucous and specialized serous glands, which occur independently or may co‐occur. Distinctive characteristics related to these glands are shape, aspect of the secretion, disposition, and distribution. The occurrences of mental and lateral glands, and the characters derived from macroscopic and microscopic examinations, have an intricate taxonomic distribution, with differing levels of homoplasy. The function of SDSGs in Cophomantini is currently unknown. However, based on structural and histochemical similarities to SDSGs from other species of amphibians where experimental evidence exists, we infer they might be involved in the secretion of chemical signals during courtship behaviour. The distribution pattern of these glands, along with the existence of different signals (i.e. acoustic, visual, tactile), suggests the presence of multimodal signalling for some species of the tribe. © 2014 The Linnean Society of London, Biological Journal of the Linnean Society, 2014, 114, 12–34.